SET‐LRP Synthesis of Well‐Defined Light‐Responsible Block Copolymer Micelles. Issue 19 (2nd September 2019) - Sedlacek, Ondrej; Filippov, Sergey K.; Svec, Pavel; Hruby, Martin
Abstract: Herein, the synthesis of well‐defined light‐sensitive amphiphilic diblock copolymers consisting of UV‐responsive poly(2‐nitrobenzyl acrylate) (PNBA) and hydrophilic poly(ethylene oxide) (PEO) blocks is reported. This is achieved by a single electron transfer living radical polymerization (SET‐LRP) of 2‐nitrobenzyl acrylate monomer initiated by PEO‐containing macroinitiator. Despite several reports on PEO‐ b ‐PNBA copolymers, this is the first time the PNBA block is synthesized by a controlled radical polymerization leading to the copolymers with low dispersity ( Ð = 1.10). In water, the copolymers self‐assemble into well‐defined micelles with a hydrodynamic diameter of 25 nm. Upon irradiation with UV‐light, the PNBA units degrade to hydrophilic poly(acrylate) resulting in disassembly of the micelles. Considering the robustness of the reported synthetic protocol, the prepared polymers represent an interesting platform for the construction of new stimuli‐responsive drug delivery systems. Abstract : Well‐defined light‐sensitive amphiphilic diblock copolymers consisting of UV‐responsive poly(2‐nitrobenzyl acrylate) (PNBA) and hydrophilic poly(ethylene oxide) blocks are synthesized by single electron transfer living radical polymerization. The copolymers self‐assemble in the aqueous environment into well‐defined micelles. Upon irradiation with UV‐light, the PNBA units degrade to hydrophilic poly(acrylate) resulting in the micelle disassembly.